Cementum attachment protein‐derived peptide induces cementum formation - Lía Hoz Rodríguez; Maricela Santana Vázquez; Luis Fernando Ramírez González; Gonzalo Montoya Ayala; Sonia López Letayf; A. Sampath Narayanan; Higinio Arzate (FASEB BioAdvances)
Abstract A pentapeptide AVIFM (CAP‐p5) derived from the carboxy‐terminus end of cementum attachment protein was examined for its role on proliferation, differentiation, and mineralization of human periodontal ligament cells (HPLC), and for its potential to induce cementum deposition in vivo. CAP‐p5 capability to induce hydroxyapatite crystal formation on demineralized dentin blocks was characterized by scanning electron microscopy, μRAMAN, and high‐resolution transmission electron microscopy. The results revealed that CAP‐p5 promoted cell proliferation and cell differentiation and increases alkaline phosphatase activity of HPLC and mineralization at an optimal concentration of 10 μg/mL. It induced the expression of cementum molecular markers BSP, CAP, CEMP1, and ALP at the protein level. In a cell‐free system, human demineralized dentin blocks coated with CAP‐p5 induced the deposition of a homogeneous and continuous mineralized layer, intimately integrated with the underlying dentin indicating new cementum formation. Physicochemical characterization of this mineral layer showed that it is composed of hydroxyapatite crystals. Demineralized dentin blocks coated with CAP‐p5 implanted subcutaneously in BALB/cAnNCrl were analyzed histologically; the results disclosed that CAP‐p5 could induce the deposition of a cementum layer intimately integrated with the subjacent dentin with cementocytes embedded into the cementum matrix. Immunostaining showed the expression of cementum molecular markers; v.gr. BSP, CAP, CEMP1 and ALP, validating the molecular identity of the newly deposited cementum. We conclude that CAP‐p5 is a new biomolecule with the potential of therapeutic application to contribute to the regeneration of cementum and periodontal structures lost in periodontal disease.